2021
DOI: 10.3802/jgo.2021.32.e87
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity in patients with gynecologic malignancies: a cross sectional study

Abstract: Objective To evaluate financial toxicity and assess its risk factors among patients with gynecologic cancers. Methods This is a cross sectional study that included 2 survey tools, as well as patient demographics, disease characteristics, and treatment regimen. Financial toxicity is measured by validated Comprehensive Score for Financial Toxicity (COST) tool. Participants were also asked to complete a 55-question-survey on attitudes and perspectives surrounding cost of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Younger age, which was associated with a lower COST score,5 explains this difference. However, in comparison with other studies in the United States among gynecologic patients, the median COST scores were also lower (19 vs 29, 20.5, and 24) 18–20. Out-of-pocket costs were not associated with the COST scores in our study.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Younger age, which was associated with a lower COST score,5 explains this difference. However, in comparison with other studies in the United States among gynecologic patients, the median COST scores were also lower (19 vs 29, 20.5, and 24) 18–20. Out-of-pocket costs were not associated with the COST scores in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Our evaluations addressed the limited sample size and reproducibility, as discussed in the validation study of the Japanese version of the COST tool 5 14. The expansion of the concept of financial toxicity has led to more studies using the COST tool being published, including studies in the field of gynecologic oncology 18–20. Our results support the reliability of financial toxicity studies.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although gynecologic malignancies are common and responsible for an estimated $3.8 billion in annual expenditures [10], study of FT in this area has been limited to several single-institutional studies [11,12]. In a study of 308 gynecologic oncology patients, Esselen et al found nearly 50% of patients to be at risk for moderate to severe FT [12].…”
Section: Introductionmentioning
confidence: 99%